Role of miRNA-181a-2-3p in cadmium-induced inflammatory responses of human bronchial epithelial cells - Kim, Jeeyoung; Kim, Dong Yeop; Heo, Hye-Ryeon; Choi, Sun Shim; Hong, Seok-Ho; Kim, Woo Jin (Journal of Thoracic Disease, 2019)
Background: Inflammation is an important priming event in the pathogenesis of pulmonary diseases, including chronic obstructive pulmonary disease (COPD). Increasing evidence indicates that microRNAs (miRNAs) contribute to the pathogenesis of COPD by regulating inflammatory response. Therefore, it is necessary to investigate novel molecular targets in COPD without any validation in COPD samples in airway inflammation. The aim of our study is to reveal novel miRNAs that can influence molecular targets for COPD and to examine the underlying mechanism in airway inflammation. Methods: We identified the downregulation of miR-181a-2-3p in the serum of COPD patients and further investigated the role of miR-181a-2-3p in cadmium (Cd)-induced inflammation of a human bronchial epithelial cell line (BEAS-2B) and normal human bronchial epithelial (NHBE) cells. Results: Our results showed that expression of miR-181a-2-3p was significantly decreased in Cd-treated cells and silencing of miR-181a-2-3p enhanced Cd-induced inflammatory responses and inflammasome activation. This negative regulatory effect of miR-181a-2-3p on inflammation is partly mediated by the calcium signaling pathway. Furthermore, global gene expression profiling revealed that Toll-like receptor 4 or sequestosome 1 genes were identified as potential targets of miR-181a-2-3p, which were significantly upregulated by knockdown of miR-181a-2-3p in Cd-treated cells. Conclusions: Our results strongly suggest that miR-181a-2-3p has a critical role in Cd-induced inflammation of airway by regulating its potential target genes, which could be molecular targets for COPD.